Road verges are refuges for small mammal populations in extensively managed Mediterranean landscapes - Ruiz-Capillas, Pablo; Mata, Cristina; Malo, Juan E (Biological Conservation, 2013)
Understanding how roads affect the persistence of animal populations is one of the challenges of road ecology. Small mammals are of great interest on account of their value as indicators of environmental impacts and their key role in ecosystems. Nevertheless, there is a large gap in our knowledge of small mammal communities in the proximity of roads. An intensive study was conducted of the effect of a motorway on the small mammal communities in an extensively managed Mediterranean landscape. Live-trapping methods were used over a 2-year period to characterise the structure and dynamics of small mammal populations at increasing distances from the motorway (0–500–1000 m). In total, 1004 individuals of three species were captured. All three were signiﬁcantly more abundant nearest to the motorway. In addition, in the case of the wood mouse, a higher proportion of juveniles was found at 0 m and 500 m from the motorway and its abundance was independent of other, habitat-related, characteristics. The greater abundance of small mammals in close vicinity to the motorway became more obvious during the second year, when a population crash reduced captures by over 60%. Thus, the ratio of captures alongside the motorway relative to those at the other distances analysed rose from approximately 3:2 to 9:2. The results point to roadside verges being an important refuge for small mammals in terms both of greater abundance and population stability. This ﬁnding has important implications from the viewpoint of conservation biology and for management of the environmental impacts of roads.
Keywords: Apodemus sylvaticus; Habitat degradation; microhabitat; Motorway; Population crash; rodents